THE ROLE OF AGRICULTURE IN THE COUNTRY'S ECONOMY - Sirojiddinov Asliddin Abduvahidjon ugli; Zafarova Nozimakhon Khushyorjon qizi (Galaxy International Interdisciplinary Research Journal, 2022)
In order to prevent the rise in prices for fruits and vegetables in the domestic market it has been established the Republican Commission for Monitoring and Control of Prices for the main types of socially important food products. Measures were taken to provide the market with scarce and high-priced products through imports and the parameters for the collection of more than 490,000 tons of the main types of agricultural products for the winter-spring season were approved by regions.